Oracle Acquired AI Startup DataFox - Singh, Netra Pal (Industrija, 2019)
All the major artificial intelligence based product and service providers in the software industry are acquiring the AI startup to enhance the existing features and capabilities of their offerings to customers. Oracle is no exception to this strategy. It has acquired DataFox to enhance AI powered capabilities, expand available data sources for its business intelligence software. This paper is an attempt to study various facets of DataFox acquisitions such as deal itself, DataFox capabilities (products/applications, customers, competitors), reasons for Oracle to acquire DataFox, and its impact on exiting products and applications of Oracle. In addition, the paper compares the acquisition with the model suggested by Bonzom and Netessine (2016) and concludes it is more for innovation, change in culture, reaching new markets, and having AI platform and less for problem solving by analysing nine propositions.